Characterization of immune response to oral administration of Streptococcus sobrinus ribosomal preparations in liposomes. - Gregory, R L (1986)
Gnotobiotic rats gastrically intubated with a total of 12.5 micrograms of Streptococcus sobrinus ribosomal protein incorporated into cholesterol-based liposomes had significantly (P less than or equal to 0.01) fewer carious lesions on their molar surfaces than did nonimmunized infected controls after challenge with a virulent organism. The immunized animals had significantly (P less than or equal to 0.01) lower numbers of molar-adherent S. sobrinus cells and higher levels of salivary immunoglobulin A antibodies to S. sobrinus whole cells and ribosomes than did the control group. Dose-response studies indicated that 12.5 micrograms of S. sobrinus ribosomal protein in liposomes induced slightly higher immune responses than did 62.5, 125.0, and 250.0 micrograms of ribosomal protein incorporated into liposomes. Intubation of rats with up to 250.0 micrograms of S. sobrinus ribosomal protein alone was no more effective in reducing the numbers of molar-adherent S. sobrinus cells than were nonimmunized infected controls, establishing that insertion of ribosomes into liposomes was required for inducing an effective immune response. These results indicate that oral administration of as little as 12.5 micrograms of S. sobrinus ribosomal protein incorporated into liposomes can protect rats from caries formation after challenge with the virulent organism by inducing specific salivary immunoglobulin A antibodies which can inhibit colonization by the challenged S. sobrinus.